Electrochemical Sensors: SnO2 Nanoparticle‐Coated ZnO Nanotube Arrays for High‐Performance Electrochemical Sensors (Small 22/2014). Issue 22 (November 2014) - She, Guangwei; Huang, Xing; Jin, Liangliang; Qi, Xiaopeng; Mu, Lixuan; Shi, Wensheng
<x xml:space="preserve">Abstract</x> Dopamine as a neurotransmitter plays vital roles in the central nervous, renal, hormonal, and cardiovascular systems. On page 4685, W. S. Shi and co‐workers fabricate electrochemical sensors based on highly ordered 1D nanostructure array electrodes composed of SnO2 nanoparticle‐coated ZnO nanotubes. The 1D nanocomposite architecture not only endows the electrochemical electrodes with large surface areas, but also allows electrons to be quickly transferred along the nanotubes. These sensors exhibit excellent performance in electrochemical detection of dopamine. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>